An experimental investigation on the dissimilar joining of AA6061 and 1Cr18Ni9Ti by refill friction stir spot welding and its mechanical properties. (April 2016) - Qiao, Fengbin; Cheng, Kai; Wang, Lianfeng; Guo, Lijie
This article presents an industrial feasible approach to robustly joining dissimilar materials of AA6061-T6 and 1Cr18Ni9Ti using refill friction stir spot welding processes and the associated joints assessment. The microstructure and shear strength property tests are taken on the dissimilar joints of 2-mm-thick plates. The results indicate that the microstructure change of the joints can be categorized in stir zone, heat-affected zone, thermomechanically affected zone and base material. The 1Cr18Ni9Ti material is squeezed toward the 6061-T6 material and forms the hook tissue, which enhances the mechanical properties of the refill friction stir spot welding–enabled joints of two dissimilar materials. The shear strength of the joints increases at first and then decreases with increase in the tool rotational speed, the indentation depth, the axial force and welding time. When the welding process is carried out at the tool rotational speed of 1800 r/min, indentation depth of 2.3 mm, the axial force of 15.65 kN and the welding time in 7.5 s, the maximum shear strength of the joints can be achieved as being able to take the loading of 8650 N as experimentally tested.